Career Transition of Immigrant Young People: Narratives of Success - Borgen, William; Buchanan, Marla; Mathew, Deepak; Nishikawara, Ria (Canadian Journal of Counselling and Psychotherapy, 2021)
While a high unemployment rate is documented among immigrant young people, research also suggests that they experience success with career decision-making despite challenging circumstances (Hofferth & Moon, 2016). This study explored the career decision-making narratives of nine young people between the ages of 25 and 35 who had come to Canada when they were between the ages of 13 and 17 and who self-define as doing well in their career decision-making. Using a narrative research design, individual narrative accounts were constructed and analyzed using a thematic analysis (Braun & Clarke, 2006). The six themes that emerged from participant responses were (a) parental and family influences, (b) networking, making connections, and mentorship, (c) personal and workplace challenges, (d) peer influences, (e) the value of education, internships, and volunteering, and (f) the importance of rewarding, fulfilling work and pursuing one’s passion. Implications for career counselling practice, research, and career theory development are discussed.